The Social Content of the Conception of Morals and its Development - Kapačiauskienė, Danutė (Problemos, 1973)
In the article an attempt is made to define the social content of the conception of morals. This conception is believed to express the value of human behaviour with the view to the manifestation or human nature. Under human nature man’s vital necessity of free and conscious activity is meant. The social content or the conception of morals has been changing in the course or history and this conception in the above sense can only be applied to the society that has overcome estrangement. The conception of morals as manifestation or humanity in behaviour under such conditions would also serve as a characteristic of all-round social activity, i.e., economic and social structure, social ideas, etc.